Comparative Effects of Mulligan’s Two Leg Rotation Technique and Muscle Energy Technique on Hamstring Flexibility - Maryam Razzaq, Zahid Mehmood Bhatti, Umber Nawaz, Hafiza Muriam Ghani, Zaib-Un-Nisa, Maryam Hina, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the effects of the Mulligan two-leg rotation technique (TLR) and the Muscle Energy Technique (MET) on hamstring flexibility. Methods: The Double-blinded randomized controlled trial was conducted among 108 subjects including both males and females with the age group of 18-35 years and on examination having hamstring tightness measured by an Active Knee Extension (AKE) Test. Group A was given Mulligan’s Two leg rotation (TLR) technique with routine physiotherapy, and Group B was given Muscle energy technique (MET) with routine physiotherapy. A total of 12 sessions were given to both groups, 3 sessions per week. Data was calculated at baseline and after every 6th session. Results: Group A had 50% males and females and Group B had 53.7% males and 46.3% females. There was a significant improvement in the flexibility of the hamstring with the application of Mulligan-TLR and MET. However, the increase in AKE range of motion was higher in MET compared to the Mulligan TLR group. Mann-Whitney U test was used to compare the mean between the two groups and shows a significant difference in values of Numeric Pain Rating scale (NPRS) (P˂0.005) and AKE (P˂0.005) after 12 sessions. Conclusion: The study demonstrated that both techniques are effective in improving hamstrings flexibility but better results are shown with MET. Therefore, it is concluded that both can be administered in clinical practice for improving hamstring flexibility.